PERAN NEGARA TURKI DALAM MENGURANGI KEMISKINAN DI SOMALIA - Djohan, Gefarina; Ridwan, Nayla Rafika (Emerald: Journal of Economics and Social Sciences, 2023)
Turkey's role in helping reduce poverty in Somalia is a form of humanitarian solidarity between countries. The poverty that occurs in Somalia is quite a big disaster and has not been completely resolved. The impacts resulting from this disaster include a food crisis or scarcity that claimed many lives and an estimated 1.5 million children experienced malnutrition. Turkey's relations with Somalia are close enough that Turkey decided to provide assistance to Somalia. The assistance provided by Turkey is in the form of humanitarian assistance in the form of money, food and medical treatment. Then development assistance takes the form of infrastructure projects in the health, education and economic sectors as well as providing financial incentives to import goods and services from sending countries to receiving countries and usually takes the form of certain projects. This research uses the concept of foreign aid and looks at the national interests of the two countries, both Turkey and Somalia. The method used in this research is a qualitative research method using descriptive analysis. The data collection method uses a literature review method using secondary data.te